KEWENANGAN KEPALA DESA DALAM PENYALURAN DAN PELAPORAN BANTUAN LANGSUNG TUNAI DI DESA JASINGA KABUPATEN BOGOR JAWA BARAT TAHUN 2022: Authority of Village Head in Distribution and Reporting of Direct Cash Assistance in Jasinga Village, Bogor Regency, West Java in 2022 - Arie Pradana Putra; Reni Dwi Purnomowati (Faculty of Law, Universitas Trisakti, 2025)
One of the social problems that Indonesia still faces is the high poverty rate. Various factors contribute to this condition, including the COVID-19 pandemic that occurred in 2020. The pandemic prompted the government to launch the Direct Cash Transfer (BLT) programme aimed at the rural poor. The distribution of BLT is a form of the government's social responsibility in an effort to restore the economic conditions of villagers. The identification of the problem in this article is about the authority of the village head in managing BLT in Jasinga Village, Bogor Regency in 2022. Based on the results of the research, it is concluded that the village has a strategic position in regulating and fulfilling the needs of its community. Then, based on the principles of diversity, participation, genuine autonomy, democracy, and community empowerment, the village has the authority to implement the programme.